Atlantis (JSTOR)
Founded in 1979, Atlantis is a peer-reviewed scholarly journal published twice-yearly by the Spanish Association of Anglo-American Studies (AEDEAN). It accepts original, unpublished research articles in English by scholars from both Spain and abroad. The scope of the journal covers literatures in English, Critical Theory, thought and culture, including film, of English-speaking communities, together with studies in linguistics, discourse analysis and pragmatics. Pertinent cross-cultural and interdisciplinary analyses are welcome. Reviews of scholarly monographs and interviews are also published. No submission should be under consideration for publication elsewhere. The suitability of manuscripts for publication is determined on the basis of double-blind reports by specialists in the area.
Keywords: American Studies